Conceptual framework of economic strategy of agricultural development in the management of national economy. (Economics and region, 2017)
UDC 303.4:631.143Halatur Svetlana, Ph.D, associate professor. Dnipropetrovsk State Agrarian University of Economics. Conceptual framework of economic strategy of agricultural development in the management of national economy. The article investigates the conceptual bases of the economic strategy of agricultural development in the management of national economy. The basic requirements to be met by economic development strategy in general and agribusiness business entities. The basic components of the economic development strategy of agriculture. The basic rules and techniques used in the formation of the economic development strategy of agriculture. The main areas in which economic strategy based agriculture in the context of a market economy. Displaying agricultural economic strategy as effectively achieve the objectives of economic methods and means. In agriculture, the current development of one of the key issues are issues of enhancing economic efficiency goals. Keywords: economic strategy, agriculture, economic development, market, production, pricing, agricultural sector.